Sacred Sanpedro in Ethnoarchaeological Context. (2nd January 2019) - Sharon, Douglas
Abstract : The earliest graphic evidence for the Sanpedro cactus occurs in north-coastal Cupisnique Culture (1500–500 BC) with ceramic depictions of the cactus by itself or more frequently associated with felines and stepped volutes. In Chavin Culture (1200–500 BC), the cactus is found in lithic sculpture associated with the "Smiling God." By Moche times (AD 100–800), Sanpedro is held in the hands of hooded females depicted alone in Moche I and II. By Moche IV there is a proliferation of these females conducting curing ceremonies. An important Sanpedro association in early Moche is with mountains. By Moche IV one ceramic depicts a blood sacrifice at the foot of a five-peaked mountain which recent research has demonstrated to be Cerro Campana, a mountain invoked by contemporary curanderas located midway between Huaca de la Luna in the Moche Valley and Huaca Cao Viejo in the Chicama Valley. Cosmograms at both of these sites are mirror-images of each other. The backgrounds of these painted reliefs include images that may be slices of Sanpedro. In the two reliefs the tripartite structuring of icons expressing a "complementarity of opposites" recurs in Cuzco's Coricancha cosmogram and the organization of power objects on contemporary curandero altars (mesas). In Lambayeque Culture (AD 800–1100) the hooded female is depicted alone holding Sanpedro. In Chimú Culture (AD. 900–1470) there is a paucity of Sanpedro depictions probably reflecting a divergence of grass-roots curanderismo from a fully-formed state religion, a situation that continues to the present.